Society and puritanism in pre-revolutionary England - "Hill, Christopher" (Middlesex, 1986)
Christopher Hill suggests that there might have been non-theological reasons for supporting the Puritans, or for being a Puritan. He shows Puritanism as a living faith, answering the hopes and fears of yeoman and gentleman, merchants and artisans.
Keywords: Puritans